Odpowiedzi

2009-11-17T15:12:42+01:00
A) 2x²:6 = 3 /×6
2x²=18 /:2
x² = 9 /√
x = 3 lub x = -3

b) (x²+3x²):9=4 /×9
4x²=36 /:4
x²=9 /√
x = 3 lub x = -3

c) 3√x = 9 /()²
9x=81 /:9
x=9

d) ½+3a:4+6=3/2
3a:4 = 1½-6½
3a:4 = -5 /×4:3
a=-20:3

e) a²+6a²:4 -a²:3=2
a²+3a²:2 -a²:3=2 /×6
6a²+9a²-2a²=12
13a²=12 /:13
a²=12:13 /√
a=2√3:√13

f) 1:x²+⅔+3=14:3x² /×3x²
3+2x²+9x²=14
11x²=11 /:11
x²=1 /√
x=1 lub x=-1

g) 2√3:4+3√3:6+1 = √3:2+√3:2+1=1+2√3:2=1+√3

h) ([2+3]:8-4:3*3)²=(5:8-4)²=25:64-5+16=11+(5/8)²=11+25/64
2009-11-17T15:26:22+01:00
A)2X^2/6=3 I*6
2x^2=18 I:2
x^2=9 Ipierwiastek
x=3

b)x^2+3x^2/9=4 I*9
x^2+3x^2=36
4x^2=36 I:4
x^2=9
x=3

c)3pierwiastek z x=9
3x=81 I:3
x=27

d)1/2+3a/4+6=3/2 I*4
2+3a+24=6
3a+26=6
3a=6-26
3a=-20 I:3
a=-20/3

e)a^2+6a^2/4-a^2/3=2 I*12
12a^2+18a^2-4a^2=24
26a^2=24 I:26
x^2=0,9
x=pierwiastek0,9